Critical Period for Weed Control in Saturated and Flooded Field, and Chemical Weed Control in Direct Seeded Rice Under Saturated Condition - Mohd Yusof, Mohamad Najib (2009)
Two field experiments were conducted at MARDI station, Seberang Perai, Penang. The experiments were: 1) Critical period in saturated and flooded field (off season 2005 and main season 2005/2006); 2) Chemical weed control in saturated field (main season 2005/2006 and off season 2006). The objectives of the study were: a) to determine the critical period of weed competition under saturated and flooded field conditions; b) to determine the efficacy of herbicides in controlling weed and their subsequent effect on rice productivity under saturated field. The first study consisted of different weeding periods under saturated and flooded field conditions. Meanwhile, the second experiment evaluated ten widely used herbicides which were available in the market either individually or as mixture, and sequentially applied in direct seeded rice fields during the critical period of weed competition under saturated field condition. Results from the first experiment indicated that Summed Dominance Ratio (SDR) of weed composition was different under saturated condition compared with flooded condition for both seasons. The dominance ranking of weed groups in off season 2005 under saturated condition was sedges followed by grasses and broadleaved weeds, while in main season 2005/2006, grassy weeds was the most dominant followed by sedges and broadleaved weeds. Under flooded condition the dominance ranking of weed groups was broadleaved followed by grasses and sedges where the trend was the same in both seasons. The numbers of tillers, along with rice grain yield were significantly affected by weed competition in both saturated and flooded condition. Yield loss due to weed competition was higher in saturated condition (54.5%) than in flooded condition (35.2%). Based on the 5% level of yield loss, the critical period in off season 2005 was at 2-71days after sowing (DAS) under saturated condition, and 15-73 DAS under flooded condition. In the main season 2005/2006, the critical periods were at 1-72 DAS in saturated condition and 2-98 DAS in flooded condition.